New insights into the prognosis of intraocular malignancy: Interventions for association mechanisms between cancer and diabetes - Gu, Lingwen; Ma, Guofeng; Li, Cui; Lin, Jing; Zhao, Guiqiu (Frontiers in Oncology, 2022)
The intraocular malignancies, mostly originate from the retina and uvea, exhibit a high incidence of blindness and even death. Uveal melanoma (UM) and retinoblastoma (RB) are the most common intraocular malignancies in adults and children, respectively. The high risks of distant metastases lead to the extremely poor prognosis. Nowadays, various epidemiological studies have demonstrated that diabetes is associated with the high incidence and mortality of cancers, such as liver cancer, pancreatic cancer, bladder cancer, etc. However, the mechanisms and interventions associated with diabetes and intraocular malignancies have not been reviewed. In this review, we have summarized the associated mechanisms between diabetes and intraocular malignancy. Diabetes mellitus is a chronic metabolic disease characterized by prolonged periods of hyperglycemia. Recent studies have reported that the abnormal glucose metabolism, insulin resistance, and the activation of IGF/insulin-like growth factor-1 receptor (IGF-1R) signaling axis in diabetes contribute to the genesis, growth, proliferation and metastases of intraocular malignancy. In addition, diabetic patients are more prone to suffer severe complications and poor prognosis after radiotherapy for intraocular malignancy. Based on the common pathogenesis shared by diabetes and intraocular malignancy, they may be related in interventions and treatments. Therefore, interventions targeting the abnormal glucose metabolism, insulin resistance and IGF-1/IGF-1R signaling axis show therapeutic potentials to treat intraocular malignancy.